Screening the Whole Social-Emotional Child: Expanding a Brief SEL Assessment to Include Emotional Behavior Concerns. Issue 1 (2nd January 2023) - Elliott, Stephen Nelson; Lei, Pui-Wa; Anthony, Christopher. J.; DiPerna, James Clyde
Abstract: Universal screening of students is increasing as programs are implemented for improving social emotional learning (SEL) skills. Assessments used to conduct SEL screenings focus on social emotional strengths; however, such assessments can provide a broader characterization of students' wellbeing by concurrently screening for emotional behavior concerns (EBC). This article describes the development of brief EBC-Internalizing and EBC-Externalizing scales designed to augment the SSIS SEL Brief Scales (SSIS SEL b ) Teacher and Student Forms. To further evaluate the utility of concurrently screening for SEL and EBCs, we examined distributions of SEL scores at each EBC Concern level. Both the Teacher and Student assessments of SEL skills and EBC behaviors maximized efficiency and yielded reliable and valid scores that provide insights regarding the interplay of these behavior constructs. The SSIS SEL b and EBC scales can be administered together as the SSIS SEL b + Mental Health Scales to provide efficient measurement of the whole social emotional child. The article examines the study's limitations, follow-up research, and implications for using brief universal screenings and instructional programs to advance the wellbeing of students. Impact Statement Universal screening of children's social emotional learning (SEL) competencies has been strength focused. A meaningful percentage of students identified as functioning at competent or advanced SEL levels, however, concurrently report cooccurring internalizing or externalizing emotional behavior concerns (EBC). Thus, universal screening programs that integrate EBC and SEL measurement can better serve the whole social emotional child.